Implementation of the Peer Tutor Model to Improve Learning Outcomes in Al-Qur'an Hadith Learning at MTs Tarbiatusshibiyan - Kamsur; Nasution, Karnada (Jurnal Profesi Guru Indonesia, 2025)
The learning process is expected to enable students to master the material being taught. Therefore, the creativity of a teacher or educator is very much needed in order to achieve learning objectives, namely an interesting learning experience and good student learning outcomes. This study is a classroom action research conducted at MTs Tariyatus Shibyan, Mempawah Regency using two cycles and the research subjects were 28 grade VII students. This study aims to improve student learning outcomes in learning the Al-Qur'an Hadith by using a peer tutor model. This study is a classroom action research with four steps, namely planning, action, observation and reflection. The subjects of this study were junior high school students. The data for this study were obtained using test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the data analysis showed an increase in student learning outcomes using the tutor method with a percentage, before the cycle 56.4%, cycle I 68.3% and cycle II 82.3%. So that peer tutors can be an alternative that teachers can use in classroom learning. Based on these results, it can be concluded that the peer tutor model can be used as an alternative to overcome the problem of low student learning outcomes in learning the Al-Qur'an and Hadith.